Teachers' Perceptions and Readiness for Mobile Artificial Intelligence Integration in Elementary Education - Batubara, Hamdan Husein; Syukur, Fatah; Junaedi, Mahfud; Purwanti, Kristi Liani; Shanie, Arsan (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The integration of artificial intelligence (AI) with mobile technologies, referred to as mobile AI, has transformed elementary education by providing personalized, interactive, and accessible learning experiences; however, its successful integration is significantly influenced by teachers’ perceptions, preparedness, and pedagogical competencies. This study employed a predominantly quantitative descriptive approach, complemented by qualitative data from open-ended questions, to investigate Indonesian elementary school teachers’ perceptions and readiness to integrate mobile AI tools. The findings revealed a gap between teachers’ positive perceptions and their moderate practical readiness. Personal experience was identified as the strongest predictor of readiness, whereas cognitive understanding and practical ability were significant predictors of perceptions. The structural equation model (SEM) supported these findings and revealed that readiness results from a series of developmental sequences rather than isolated events. This study highlights the need to address both psychological and practical barriers to adoption and offers actionable recommendations for harnessing the transformative potential of mobile AI in elementary education.